Can Ricardian Model Really Explain Trade? - Kok Wooi Yap; Doris Padmini Selvaratnam (Journal of International Business, Economics and Entrepreneurship, 2018)
This paper aims to analyse the international trade in the real world by applying the Ricardian trade theory. In doing this, simple comparative advantage assumptions are used to examine trading of palm oil and rice between Malaysia and Vietnam. By using this theory, it is proven that international trade takes place because of efficiency to produce exported product. A country will export products that use its abundant and cheap factors of production and import products that use its scarce factors. Various empirical evidences of previous studies are also used to discuss the importance of the Ricardian model. However, it is also highlighted in the paper that the Ricardian model could be misleading as it has several limitations that restrict its usefulness.